(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study was conducted in four districts i.e. Udaipur, Chittorgarh, Rajsamand and Bhilwara from breeding tract of Sonadi sheep. The data on flock statistics of 6979 registered Sonadi sheep maintained by 147 shepherds of eight tehsils from four districts of Sonadi breeding tract were recorded. The overall mortality according to different seasons and age groups of Sonadi sheep was highest during summer (57.0%) as compared to winter (15.7%) and rainy (27.3%) seasons. Sonadi sheep belonging to age group of 1-3 month, 3-6month and adult, the frequency of mortality was highest during summer, while in case of sheep belonging to age group of above 6 months mortality was in rainy season. The maximum proportion sheep’s were sold in the month of July in Udaipur and in the month of May in Chittorgarh districts. Higher proportion of sheep were sold during summer as compared to winter and rainy seasons, while the sheep’s belonging to age group of 1-3 months, 3-6 months and adult were sold during summer season. The overall literacy rate had significant effect on all the parameters of land holding as well as buffalo, goat, total sheep, large ruminant, small ruminant and total livestock holding. The positive and significant association was observed between age of family head and total cattle, total other than Sonadi sheep and large ruminant population. The correlation of literacy rate with buffalo, goat, large ruminant and total livestock was found to be positive and significant.